2020
DOI: 10.1371/journal.pone.0241147
|View full text |Cite
|
Sign up to set email alerts
|

Simulating adaptation strategies to offset potential impacts of climate variability and change on maize yields in Embu County, Kenya

Abstract: In this study, we assessed the possible impacts of climate variability and change on growth and performance of maize using multi-climate, multi-crop model approaches built on Agricultural Model Intercomparison and Improvement Project (AgMIP) protocols in five different agro-ecological zones (AEZs) of Embu County in Kenya and under different management systems. Adaptation strategies were developed that are locally relevant by identifying a set of technologies that help to offset potential impacts of climate cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
3
5
0
Order By: Relevance
“…The higher rainfall variability in the OND seasonal rainfall compared to that in MAM seasonal rainfall in the research area could be a serious threat to food security since the OND seasonal rainfall is considered the main and most reliable season for crop production in the region. The results corroborate findings by Gummadi et al (2020) which indicated an increasing variability in the OND seasonal rainfall in Embu County, Kenya.…”
Section: Rainfall Trends and Variability In The Study Areasupporting
confidence: 90%
“…The higher rainfall variability in the OND seasonal rainfall compared to that in MAM seasonal rainfall in the research area could be a serious threat to food security since the OND seasonal rainfall is considered the main and most reliable season for crop production in the region. The results corroborate findings by Gummadi et al (2020) which indicated an increasing variability in the OND seasonal rainfall in Embu County, Kenya.…”
Section: Rainfall Trends and Variability In The Study Areasupporting
confidence: 90%
“…Additionally, the simulation of phenological development and grain yield at maturity were within the acceptable thresholds (< 10%) and (< 20%), respectively, according to Jamieson et al, (1991). The accuracy of the DSSAT-CERES-Maize model for maize yield simulation aligned with other studies in Kenya that calibrated and evaluated the model for various applications (Aluoch et al, 2022;Gummadi et al, 2020). In addition, other studies conducted in the wider East Africa and SSA 1 3 regions found robust accuracies in the CERES-Maize model calibration and evaluation under various managements (Chisanga et al, 2020;Mourice et al, 2015;Volk et al, 2021).…”
Section: Calibration and Evaluation Of The Dssat-ceres-maize Modelsupporting
confidence: 66%
“…In the present study, the phenological parameters (P1, P2, and P5) were calibrated by specifying 6000 runs, followed by a similar number of runs to estimate the growth parameters (G2, G3, and PHINT). The thresholds for phenological and growth parameters were guided by values obtained in other field experiments conducted in the East African region and subsequently adjusted for in the parameter file (Gummadi et al, 2020;Mourice et al, 2014).…”
Section: Dssat-ceres-maize Model Calibration and Evaluationmentioning
confidence: 99%
“…This study was conducted in the lower midland (LM3), LM4 and inner lowland (IL5) zones, whereas Sharma et al (1993) conducted their study in LM3, LM4, LM5, upper midland (UM3) and UM4 AEZs. The AEZs LM3, UM3 and UM4 are high potential agricultural areas with an annual mean rainfall of >1000 mm, altitude of 1070-1460 m and mean temperature of 19.6-22.0 C. The LM4 and LM5 are low potential agricultural areas characterized by < 1000 mm of rainfall, mean annual temperature of 21.0-23.9 C and an altitude of 830-1220 m (Jaetzold et al, 2007;Gummadi et al, 2020). For the IL5, the annual mean rainfall is <900 mm, mean annual temperature is 24.0-25.4 C and the altitude is 600-850 m (Jaestzold et al 2007).…”
Section: Discussionmentioning
confidence: 99%